The Capra touch a study of the director's Hollywood classics and war documentaries, 1934-1945 - Gunter, Matthew C., 1974- (McFarland & Co., 2012)
"During World War II, Frank Capra (1897-1991) made propaganda films for the U.S. government. These entries in the Why We Fight documentary series have been largely neglected by Capra scholars. This work analyzes the cinematic and thematic techniques Capra employed in these films, linking them to the techniques and ideology of the director's popular mainstream narrative films"--Provided by publisher.